Case representation by medical experts, intermediates and novices for laboratory data presented with or without a clinical context. - Verkoeijen PP; Rikers RM; Schmidt HG; Van De Wiel MW; Kooman JP (Medical Education, 2004)
Based on cognitive psychological research, a number of theoretical frameworks have been put forward to describe the structure of experts' medical knowledge and to explain experts' case-processing. To provide evidence for the theory of knowledge encapsulation, which states that medical knowledge constitutes of interlinked biomedical and clinical knowledge. Fourth-year medical students, clerks and medical experts evaluated six case descriptions, consisting of laboratory data either with or without a clinical context. For each case description, the participants were required to study the case, to formulate a diagnosis, and to write down everything they could remember of the case. When the laboratory data were not embedded within a clinical context, medical experts' case-processing increased and their diagnostic accuracy became worse. Furthermore, laboratory data recall of medical experts was more elaborate in cases where the laboratory data were presented without a clinical context. Similar results were obtained for students and clerks. The findings are only partially consistent with a prediction made by the theory of knowledge encapsulation. Further research, using a different paradigm than the traditionally used method of free recall, is required to unearth whether medical experts use qualitatively different knowledge structures than novices while solving cases.